Reported healthcare-seeking of loiasis patients and estimation of the associated monetary burden in Gabon: Data from a cross-sectional survey. - Luzia Veletzky; Veronika Schlicker; Jennifer Hergeth; Daniel R Stelzl; Rella Zoleko Manego; Ghyslain Mombo-Ngoma; Kirsten Alexandra Eberhardt; Matthew B B McCall; Ayôla A Adegnika; Bertrand Lell; Benjamin Mordmüller; Scherif Adegnika; et al. (Public Library of Science (PLoS), 2024)
Background Loiasis is a disease of relevance in endemic populations and there has been advocacy for its inclusion on the World Health Organization's neglected tropical diseases list. As loiasis-related healthcare-seeking behaviors and related costs are unknown, we aimed to evaluate these aspects in a population residing in an endemic region in Gabon. Methods Data were collected during a community-based, cross-sectional study assessing the disease burden due to loiasis. Diagnostics for microfilaremia were performed and a history of eyeworm was obtained. In addition, a standardized questionnaire about type of healthcare resources and frequency of use, as well as respective associated costs was administered to each participant. Loiasis related healthcare-seeking behaviors were evaluated, and the associated monetary burden was estimated as a secondary outcome of the study. Findings Individuals diagnosed with loiasis more frequently reported any healthcare-seeking (OR 1.52 (95%CI: 1.21-1.91)), self-medicating (OR 1.62 (1.26-2.08)), inability to work (OR 1.86 (1.47-2.35)), and consulting with traditional healers (logOdds 1.03 (0.52-1.53)), compared to loiasis negative individuals. The most frequently reported treatment for the eyeworm was traditional herbs. The estimated healthcare associated costs, per positive individual, was US-$ 58 (95% CI: 21-101) per year, which would correspond to 3.5% of the reported mean household income. Extrapolation to the rural population of Gabon (n = 204,000), resulted in an annual monetary burden estimate of US-$ 3,206,000 (1,150,000-5,577,000). Interpretation Loiasis patients have demonstrated healthcare needs, often consulted traditional healers, and used traditional treatments for disease specific symptoms. Further, loiasis seems to be associated with substantial direct and indirect costs for individuals and thus may cause a relevant economic burden for endemic populations and economies of affected countries.